The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18632/aging.204200
|View full text |Cite
|
Sign up to set email alerts
|

M1 macrophage-derived exosomes synergistically enhance the anti- bladder cancer effect of gemcitabine

Abstract: Gemcitabine (GEM) is one of the first choice drugs for treating bladder cancer. In this study, we loaded M1 macrophage-derived exosomes (M1-Exo) with GEM by ultrasonication technique to derive an M1-Exo-GEM drug delivery system, and then explored its effects on bladder cancer. After inducing M1 polarization of macrophages in vitro, ultracentrifugation was performed to obtain M1-Exo, followed by construction of M1-Exo-GEM via ultrasonication technique. Mouse bladder cancer MB49 cells were chosen for study. CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In another study, M1-Exo-GEM (pre-loading M1 macrophage-derived exosomes(M1-Exo) with Gemcitabine (GEM) by ultrasound technology) was built up for killing mouse bladder cancer MB49 cells. Compared with M1-Exo and GEM, M1-Exo-GEM had significantly up-regulated the expression of inflammatory cytokines and stronger cytotoxic effect on cancer cells [ 100 ].…”
Section: Other Systemic Diseasesmentioning
confidence: 99%
“…In another study, M1-Exo-GEM (pre-loading M1 macrophage-derived exosomes(M1-Exo) with Gemcitabine (GEM) by ultrasound technology) was built up for killing mouse bladder cancer MB49 cells. Compared with M1-Exo and GEM, M1-Exo-GEM had significantly up-regulated the expression of inflammatory cytokines and stronger cytotoxic effect on cancer cells [ 100 ].…”
Section: Other Systemic Diseasesmentioning
confidence: 99%
“…Meanwhile, several groups have successfully demonstrated the use of macrophage-derived exosomes to improve therapeutic efficacy and drug delivery for cancer treatments. Tang et al obtained exosomes from M1 phenotype macrophages by treating raw 264.7 cells with LPS and IFN-γ and found that they express higher levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β, thereby exacerbating the cytotoxic effects of gemcitabine on mouse bladder cancer [41]. Incorporation of paclitaxel into exosomes derived from raw 264.7 cells could enhance the cytotoxicity by more than 50 times in multi-drug resistant cancer cells with effective tumor site delivery observed in a mouse model of pulmonary metastases [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang and his group prepared PTX-loaded EXOs isolated from murine macrophages [ 74 ]. In particular, through sequential centrifugations, the EXOs were isolated from lipopolysaccharide-activated M1 macrophages, able to produce EXOs with documented antitumor activity [ 113 ]. PTX was loaded through sonication followed by incubation at 37 °C, to restore the EXO membranes, obtaining a DL of 19%.…”
Section: Plant Derivatives Vehiculated In Exos and Biomimetic Hybrid ...mentioning
confidence: 99%